Root Reconstruction with Total Replacement of Ascending Aorta Using Hypothermic Circulatory Arrest and Selective Cerebral Perfusion for Moderately Dilated Distal Ascending Aorta - Yamashiro, Satoshi; Arakaki, Ryoko; Kise, Yuya; Inafuku, Hitoshi; Kuniyoshi, Yukio (Scientific Research, 2013)
Objective: We have occasionally encountered a moderately dilated distal ascending aorta while reconstructing an aortic root. We describe reconstruction of an extended root and ascending aorta using our current strategy. Patients and Methods: Between March 2011 and December 2012, 15 (11 men; mean age, 70.1 ± 7.3 years) patients underwent root reconstruction with hemi-arch replacement under hypothermic circulatory arrest with antegrade selective cerebral perfusion. The maximum diameter of the aortic root was 52.5 ± 4.4 mm. The distal ascending aorta just below innominate artery was moderately dilated to 41.7 ± 1.4 mm in diameter. Results: Operative outcomes excluding the diameter of the distal ascending aorta did not significantly differ from those of patients who had undergone root reconstruction under distal ascending aortic clamping during the same period. Postoperative computed tomography confirmed complete resection of the dilated ascending aorta in the patients, and did not develop neurological dysfunction or stroke. Conclusion: Postoperative computed tomography confirmed complete resection of dilated ascending aortae. We considered that complete resection under hypothermic circulatory arrest and selective cerebral perfusion might help to avoid repeated surgery to treat dilation of the distal ascending aorta over the long-term
Keywords: Annulo-Aortic Ectasia; Re-Operation